2018
DOI: 10.1371/journal.pone.0200021
|View full text |Cite
|
Sign up to set email alerts
|

Purification and identification of two novel antioxidant peptides from perilla (Perilla frutescens L. Britton) seed protein hydrolysates

Abstract: Proteins were extracted from perilla (Perilla frutescens L. Britton) seed by-products and hydrolyzed with an alkaline protease. Antioxidant peptides were purified from the hydrolysate by size-exclusion chromatography and RP-HPLC. Two peptides with strong antioxidant activity were identified as Tyr-Leu (YL) and Phe-Tyr (FY) with the molecular mass of 294.33 Da and 328.33 Da, respectively. Synthesized YL and FY efficiently quenched free radicals (DPPH, ABTS and hydroxyl radicals) and showed high oxygen radical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 31 publications
4
38
0
Order By: Relevance
“…Therefore, the presence of hydrophobic residues in the APYMM (A, P, Y and M), FWIIE (F, W and I) and MWTD (M and W) sequences may be critical for inhibition of lipid peroxidation by the three peptides. The three peptides isolated from Chinese mutton ham showed stronger inhibitory effects on linoleic acid oxidation than those reported for Perilla frutescens seed protein hydrolysates . Therefore, these Chinese MHPs could be used as additives in fatty foods to extend their shelf life.…”
Section: Resultsmentioning
confidence: 84%
“…Therefore, the presence of hydrophobic residues in the APYMM (A, P, Y and M), FWIIE (F, W and I) and MWTD (M and W) sequences may be critical for inhibition of lipid peroxidation by the three peptides. The three peptides isolated from Chinese mutton ham showed stronger inhibitory effects on linoleic acid oxidation than those reported for Perilla frutescens seed protein hydrolysates . Therefore, these Chinese MHPs could be used as additives in fatty foods to extend their shelf life.…”
Section: Resultsmentioning
confidence: 84%
“…However, the extract tested in this previous study was processed and purified more extensively (as discussed above) to concentrate the rosmarinic acid content, compared with the Eth extract tested in the present study, which could be more chemically typical of the nutlets from P. frutescens that could be developed for herbal/nutraceutical product applications. Another recent study concluded that two peptides from P. frutescens seed protein hydrolysates are also antioxidant via inhibition of lipid peroxidation in rat liver and HepG2 cells in vitro (Yang et al, ). However, in this study, the plant material investigated was obtained from a local market, and there is no indication that the plant material was botanically verified as seeds from this species.…”
Section: Discussionmentioning
confidence: 99%
“…The second methods work based on electron transfer in which an antioxidant is estimated by comparing it with a certain oxidant ( Zou et al., 2016 , Zou et al., 2016 ). These methods include ferric ion reducing antioxidant power (FRAP), trolox equivalent antioxidant capacity (TEAC), hydroxyl (OH) radical scavenging activity, DPPH radical-scavenging capacity (DPPH), superoxide anion radical-scavenging (O 2 ) activity and superoxide dismutase (SOD)-like activity ( Barkia, Al-haj, Hamid, Zakaria and Saari, 2018 ; Chen et al., 2019 , Chen et al., 2019 ; Iskandar et al., 2015 ; Yang et al., 2018 ). Tables 1 and 2 shows some examples of antioxidant activity evaluation methods for selected protein hydrolysates and peptides.…”
Section: Antioxidant Peptidesmentioning
confidence: 99%
“…Various food derived protein sources have been utilized to produce bioactive peptides. For example, plant sources, such as walnut meal proteins ( Feng et al., 2018 ), hazelnut protein ( Liu et al., 2018 ), sesame protein ( Lu et al., 2019 ), perilla seed protein ( Yang et al., 2018 ), soybean ( Chen et al., 2018 ), common bean ( Chen et al., 2019 , Chen et al., 2019 ) and protein from cauliflower by-products ( Montone et al., 2018a ); animal sources, such as goat, sheep and bovine milk proteins ( Moreno-montoro et al., 2018 ; Tagliazucchi et al., 2018 ; Zanutto-elgui et al., 2019 ), egg ( Wang et al., 2018 ; Eckert et al., 2018 ) and ham ( Xing et al., 2018 ); fish and their by-products, such as salmon ( Neves et al., 2017 ), stone fish protein ( Auwal et al., 2017 ), chub marckerel ( Bashir et al., 2017 ), turbot skin ( Fang et al., 2017 ), shrimp shell discards ( Ambigaipalan and Shahidi, 2017 ), tilapia frame and skin ( Huang et al., 2015 ); and microalgae proteins, such as blue-green algae ( Seddek et al., 2019 ), Irish brown seaweed Ascophyllum nodosum ( Kadam et al., 2016 ), Tetradesmus obliquus microalgae ( Montone et al., 2018b ), have been reported as sources of bioactive peptides.…”
Section: Introductionmentioning
confidence: 99%